ANALISIS POLA KONSUMSI DAN KETIMPANGAN PENDAPATAN DI PROVINSI SULAWESI TENGAN TAHUN 2013 - Paskual, Meity Ferdiana (Katalogis, 2018)
This research is categorised as descriptive quantitative. The results show that (1) Central Sulawesi Province has consumption patterns which are more likely in food consumption. The consumption patterns follow the Law of Engels where a decline in the percentage of food consumption on any increase in revenue. At the same time, the percentage of non-food consumption continues to rise. The largest component of household consumption in Central Sulawesi as follow: (i) housing and household facilities, (ii) various goods and services, (iii) grains, (iv) for foods and drinks, as well as (v) tobacco and betel. (2) According to the World Bank, the inequality of Central Sulawesi Province is categorised as low and moderate with Gini Ratio = 0.39. Therefore, it needs special attention by the government because the number of Gini Ratio is approaching the limit of high inequality. (3) The pattern of consumption in the districts or cities in Central Sulawesi Province can be distinguised as follow; the household spending in several regencies, such as, Banggai Islands, Poso, Donggala, Tolitoli, Buol, Parigi Moutong, Tojo Una-Una and Sigi are more likely to consume food. Meanwhile, the household spending in Palu, Morowali and Banggai Regencies are more likely to consume non-food consumption. However, the three regions have higher level of inequality compare to other areas. It is due to non-food consumption is dominated by high-income households.